Neurological screening of preterm infants with peri- and intra-ventricular hemorrhage: observation transversal study - Maglione, Andréa Vancetto; Golin, Marina Ortega; Sarni, Roseli Oselka Saccardo (ABCS Health Sciences, 2018)
Introduction: Preterm infants with less than 27 weeks of gestacional age present vulnerability for development of periand intraventricular hemorrhage (PIVH). This can affect the myelinization and organization of cerebral cortex, leading to possible developmental impairment. Objective: To evaluate the neurological behavior of preterm infants affected by PIVH with and without sepsis according to the Dubowitz Method summary, to delimit the presence of deviant items of the evaluation and to compare with the results of the control group (without PIVH). Methods: This is a cross-sectional study. The preterm infants were divided in three groups, two study groups (PIVH and PIVH + sepsis), and one control group. The summary version of the Dubowitz Method was used as a neurological screening for the risk in preterm infants. The analysis was performed according to scores with deviation in these items and compared to the expected normal score. Data obtained were compared using the summary score and the full version of the test. Results: The frequency of abnormal scores was: 40% in the group with PIVH + sepsis, 10% in the group only with PIVH, 15% in the control group. Conclusion: The PIVH does not seem to be a significant factor for the presence of items with deviation in the summary version of Dubowitz Method. The presence of PIVH in more severe stages was associated with the presence of sepsis. The preterm infants with PIVH with sepsis obtained worse neurological performance in the test.